Persistensi Laba: Pengaruh Leverage, Akrual, dan Arus Kas Pada Emiten Manufaktur Indonesia - Kurnia, Denny; Hapsari, Denny Putri (Lembaga Penelitian Universitas YARSI, 2026)
This study examines the determinants of earnings persistence in Indonesian manufacturing firms, focusing on leverage, accruals, and operating cash flow. It aims to provide empirical evidence on how financial structure and earnings components influence earnings sustainability in an emerging market context. Using purposive sampling, the study analyzes 90 manufacturing companies listed on the Indonesia Stock Exchange during 2019–2021. Secondary data were obtained from published annual financial statements and analyzed using multiple linear regression with SPSS version 25. The results show that leverage, accruals, and operating cash flow each have a statistically significant effect on earnings persistence. Leverage has a negative impact (β = −0.108; p < 0.01), indicating that higher debt levels reduce earnings sustainability. Accruals exhibit the strongest negative effect (β = −0.680; p < 0.001), suggesting that accrual-dominated earnings are less persistent. Operating cash flow also negatively affects earnings persistence (β = −0.564; p < 0.001), reflecting sensitivity to cash flow volatility. Overall, the model explains 26.5% of the variation in earnings persistence. These findings emphasize the importance of prudent leverage management, high-quality accruals, and stable cash flows to enhance long-term earnings sustainability.